(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Salinity is a significant abiotic stress that limits plant growth and profitability in numerous areas of the world because of the increasing use of helpless water quality for water systems and soil salinization. Complex physiological characteristics, metabolic pathways, and atomic or quality networks are involved in plant variation or resistance to salinity pressure. Diverse versatile responses to salinity stress at sub-atomic, cell, metabolic, and physiological levels have been recognized in late research, in spite of the fact that the mechanisms underlying salinity resistance are a long way from completely understood. This paper offers a comprehensive audit of significant advances in research on biochemical, physiological, and atomic mechanisms that control plant transformation and salinity stress resilience.